Los problemas del poder: política local y gobierno en las reducciones de la costa de Piura, siglo XVII - Diez, Alejandro (2006)
Local power may be understood either as a government, shaped on the basis of social relationships and institutions, that adjusts to social structures, or as a series of mechanisms and procedures of symbolic mobilization generating the effect that an order is required for daily coexistence. In a territorialized space, both approaches are complemented and shape the areas where local power operated. This article analyzes local power in the Indian towns of San Juan de Catacaos and San Martín de Sechura (in the coast of Piura), in the context of the making up of the government structures that the colonial regime imposed. The author focuses on the figure of the colonial cacique, on the mechanisms he used to have access to power and to legitimate it, on the interests he mobilized according to his obligations with the colonial regime and with the Indians living in his territory (parcialidad), as well as on the spheres of influence of local power both at the reducciones and at the larger arenas of the Corregimiento de Piura and the colonial State.